2015
DOI: 10.1016/j.procir.2015.02.187
|View full text |Cite
|
Sign up to set email alerts
|

Learning Factories for Research, Education, and Training

Abstract: Acknowledgements The research team acknowledges the assistance of Frances Plummer and Kevin Bradburn, NSW DET; the teachers of the nine case study schools who were welcoming, open and supportive of this research; the many teachers in Quality Teaching Action Learning projects, who responded to surveys or took the time to engage in conversations with the researchers; Kate Aubusson for research assistance; and the support staff at the Faculties of Education at the University of Technology, Sydney and the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(145 citation statements)
references
References 13 publications
2
119
0
24
Order By: Relevance
“…Lorenz and co-workers [11] also observed that in Industry 4.0, manual repetitive tasks and many jobs of a cognitive nature (such as production planning) will be eliminated. In addition, Abele et al [18] have discussed the effects of Industry 4.0 and noted that "the classic production job profile like industrial engineer increasingly has to dive into the world of information and communication technology to cope with the modelling of complex processes and systems".…”
Section: Industrial Engineering Education and Industry 40mentioning
confidence: 99%
“…Lorenz and co-workers [11] also observed that in Industry 4.0, manual repetitive tasks and many jobs of a cognitive nature (such as production planning) will be eliminated. In addition, Abele et al [18] have discussed the effects of Industry 4.0 and noted that "the classic production job profile like industrial engineer increasingly has to dive into the world of information and communication technology to cope with the modelling of complex processes and systems".…”
Section: Industrial Engineering Education and Industry 40mentioning
confidence: 99%
“…Learning by doing has been shown to lead to greater application and retention possibilities than the traditional methods of education such as lectures [7], [9]- [11]. Due to the knowledge transfer resulting from real production conditions, favoured over a purely theoretical exposition, learning factories can also be used to train employees.…”
Section: Opsommingmentioning
confidence: 99%
“…In the teaching industry program students are given more opportunities to perform work like a worker so there is a skill improvement ( [11]; [12]; [13]; [14] [15]). Teaching industry or teaching industry not only provides benefits to students, but also provides benefits for educators ( [16]; [17]). Parties in the teaching factory that industry and academic incorporate new technology into the curriculum in education ( [18]; [19]).…”
Section: A Teaching Factorymentioning
confidence: 99%